Development and validation of a prototype for the on-line simultaneous analysis of quality caprolactam synthesized on an industrial scale (2022)
Caprolactam is a highly useful monomer obtained through the Beckmann arrangement, which generates large profits worldwide and is widely used in different industries. During the synthesis process, various components can be generated that weaken the quality of the final product, to have control of the monomer, monitoring is carried out during the synthesis and characterization of the final product. These characterizations generally take time due to the different techniques that must be performed to obtain the data. In this work, a method is designed that associates different techniques to reduce the number of steps carried out in the tests to determine the qual- ity of the material, optimize the times and generate a quality and efficient process in a shorter time, in addition, it is due to a semi-automated system for the simultaneous characterization of caprolactam, which, according to the statistical data obtained for sodium, iron, volatile bases, and moisture analysis were reproducible. The developed prototype had 21 on-line valves that allowed taking the representative volumes of samples and reagents necessary for each measure- ment. There is excellent linearity where the correlation coefficient has values between 0,9992 and 1. The values obtained for the relative error are between 0.18 and 2.24% for laboratory tests using the traditional method and between 0.21 and 3.83% for tests carried out using the proto- type. The P value of the evaluation of the means was 0.997, indicating that the means are not statistically different.